Cathodic reducing bacteria of dual-chambered microbial fuel cell. (9th November 2017) - Zhang, Guodong; Feng, Sansan; Jiao, Yan; Lee, Duu-Jong; Xin, Yanjun; Sun, Huifang
Abstract: Bacteria on biocathode can facilitate cathodic reduction reaction for a microbial fuel cells. This study profiled the cathodic bacterial community with high reduction activity using the Illumina pyrosequencing method, from which the highly diversified and novel population structure was found. The cathodic biofilm had a community structure dominated by Proteobacteria (42.7%), Firmicutes (25.0%), 9.7% Bacteroidetes (9.7%), Actinobacteria (7.7%) and Aquificae (7.1%). And the species of Acidovorax, Soehngenia, Clostridium, Sulfurihydrogenibium, Flexibacter, Mycobacterium and others were the predominant populations. Function composition analysis showed that the membrane transport is the most important metabolic activity for this community. Highlights: Bacterial community on biocathode of microbial fuel cell was profiled. Highly diversified community with rare species was noted. Membrane transport is the most important metabolic activity for this community.